Fatigue Life Prediction of the Keel Structure of a Tsunami Buoy Using Spectral Fatigue Analysis Method - Yustiawan, Angga; Suastika, Ketut; Nugroho, Wibowo Harso (UI Scholars Hub, 2013)
One of the components of the Indonesia Tsunami Early Warning System (InaTEWS) is a surface buoy. The surface buoy is exposed to dynamic and random loadings while operating at sea, particularly due to waves. Because of the cyclic nature of the wave load, this may result in a fatigue damage of the keel structure, which connects the mooring line with the buoy hull. The operating location of the buoy is off the Java South Coast at the coordinate (10.3998 S, 108.3417 E). To determine the stress transfer function, model tests were performed, measuring the buoy motions and the stress at the mooring line. A spectral fatigue analysis method is applied for the purpose of estimating the fatigue life of the keel structure. Utilizing the model-test results, the S-N curve obtained in a previous study and the wave data at the buoy location, it is found that the fatigue life of the keel structure is approximately 11 years.